Simple and efficient enzymatic transglycosylation of stevioside by beta-cyclodextrin glucanotransferase from Bacillus firmus - Jaitak, V.; Kaul, V. Kumar; Bandna; Kumar, N.; Singh, B.; Savergave, L. S.; Jogdand, Vitthal V.; Nene, S. (Biotechnology Letters, 2009)
Stevioside was subjected to 1,4-intermolecular transglycosylation using beta-cyclodextrin glucanotransferase (beta-CGtase) produced from an alkalophilic strain of Bacillus firmus. The reaction was carried out by traditional, ultrasound-assisted and microwave-assisted techniques. Reaction under microwave conditions was faster and was completed in 1 min yielding two 1,4 transglycosylated products, 4'-O-alpha-d-glycosyl stevioside (I) and 4''-O-alpha-d-maltosyl stevioside (II) in 66% and 24%, respectively. The optimum transglycosylation occurred by using stevioside (1.24 mmol), beta-CD (1.76 mmol) and beta-CGtase (2 U/g) under microwave assisted reaction (MAR) in 5 ml sodium phosphate buffer (pH 7) at 50A degrees C and 80 W power. MAR is therefore potentially a useful and economical method for faster transglycosylation of stevioside.
13th International Biotechnology Symposium and Exhibition (IBS-2008), Dalian, PEOPLES R CHINA, OCT 12-17, 2008
Keywords: beta-cyclodextrin; beta-Cyclodextrin glucanotransferase; Microwave-assisted reaction; Stevia rebaudiana; Stevioside; Transglycosylation